BRIM aid too much: Scholar tells govt - Daily Express, (KK) (Daily Express (KK), 2014)
KUALA LUMPUR: Aid in the form of cash handouts should be minimised if the government is to effectively address the fiscal deficit problem, said academician Dr Irwan Shah Zainal Abidin.